Skeletal survey yields in low vs. high risk pediatric patients with skull fractures. (May 2023) - Isaac, Reena; Greeley, Christopher; Marinello, Mark; Herman, Bruce E.; Frazier, Terra N.; Carroll, Christopher L.; Armijo-Garcia, Veronica; Musick, Matthew; Weeks, Kerri; Haney, Suzanne B.; Wang, Ming; Hymel, Kent P.; et al.
Abstract: Background: To assess for occult fractures, physicians often opt to obtain skeletal surveys (SS) in young, acutely head-injured patients who present with skull fractures. Data informing optimal decision management are lacking. Objective: To determine the positive yields of radiologic SS in young patients with skull fractures presumed to be at low vs. high risk for abuse. Participants and setting: 476 acutely head injured, skull-fractured patients <3 years hospitalized for intensive care across 18 sites between February 2011 and March 2021. Methods: We conducted a retrospective, secondary analysis of the combined, prospective Pediatric Brain Injury Research Network (PediBIRN) data set. Results: 204 (43 %) of 476 patients had simple, linear, parietal skull fractures. 272 (57 %) had more complex skull fracture(s). Only 315 (66 %) of 476 patients underwent SS, including 102 (32 %) patients presumed to be at low risk for abuse (patients who presented with a consistent history of accidental trauma; intracranial injuries no deeper than the cortical brain; and no respiratory compromise, alteration or loss of consciousness, seizures, or skin injuries suspicious for abuse). Only one of 102 low risk patients revealed findings indicative of abuse. In two other low risk patients, SS helped to confirm metabolic bone disease. Conclusions: Less than 1 % of low risk patients under three years of age who presented with simple or complex skull fracture(s) revealed other abusive fractures. Our results could inform efforts to reduce unnecessary skeletal surveys.